Social Autopsy a Tool for Maternal and Perinatal Death Surveillance and Response (MPDSR) Reporting in Pakistan: Social Autopsy: A Tool for Maternal and Perinatal Death - Idrees, Fahmeeda; Ahmad, Saeed; Waheed, Eman; Rubab, Bisma; Abbas, Faiza (Pakistan Journal of Health Sciences, 2022)
Social autopsy is a relatively new technique to report non-biological causes of death along with biological causes, which accounts for 12/15 maternal deaths in Pakistan, through direct interaction with the community. Pakistan had a highest neonatal mortality in the entire world. A significant number of unreported cases contributed to the high prevalence of neonatal and maternal mortality. Pakistan is one of the top 10 nations that contribute to 60% of maternal and perinatal deaths worldwide which demands social autopsy adoption in Pakistan. Information acquired by social autopsy will therefore be useful in developing any efforts to stop or treat causes linked with death. Social autopsy is a way of health promotion as it encourages individual and communal behavioral change and contributes in achieving United Nations Sustainable Development Goal (SDG) 3.1 by reducing maternal and perinatal death mortality by 2030 and 2035 respectively. In discussion with the family of a woman and community, health workers examine the social reasons of death and pinpoint reforms that are required. In Bangladesh, Brazil, Tanzania, India and Nigeria, maternal and perinatal deaths have been lowered due to adoption of social autopsy. Pakistan has embraced verbal autopsy, but it is an ineffective technique which just deals with the medical cause of death. Maternal and perinatal deaths are not just because of medical causes, it is also the result of interactions between several social, cultural and economic factors. Government of Pakistan is just spending 0.8% of its GDP on health. Standard of primary maternity care is generally unsatisfactory. Only 25% basic health units have qualified staff. Government of Pakistan should create a provincial MPDSR committee, strengthen the health care network and pilot social autopsy in Pakistan to meet SGD goal 3.